ChatGPT and autoimmunity – A new weapon in the battlefield of knowledge - Darkhabani, Mohammad; Alrifaai, Mohamad Aosama; Elsalti, Abdulrahman; Dvir, Yoad M.; Mahroum, Naim (Elsevier B.V., 2023)
The field of medical research has been always full of innovation and huge leaps revolutionizing the scientific world. In the recent years, we have witnessed this firsthand by the evolution of Artificial Intelligence (AI), with ChatGPT being the most recent example. ChatGPT is a language chat bot which generates human-like texts based on data from the internet. If viewed from a medical point view, ChatGPT has shown capabilities of composing medical texts similar to those depicted by experienced authors, to solve clinical cases, to provide medical solutions, among other fascinating performances. Nevertheless, the value of the results, limitations, and clinical implications still need to be carefully evaluated. In our current paper on the role of ChatGPT in clinical medicine, particularly in the field of autoimmunity, we aimed to illustrate the implication of this technology alongside the latest utilization and limitations. In addition, we included an expert opinion on the cyber-related aspects of the bot potentially contributing to the risks attributed to its use, alongside proposed defense mechanisms. All of that, while taking into consideration the rapidity of the continuous improvement AI experiences on a daily basis.
Keywords: Artificial Intelligence; Autoimmunity; Chat Bots; ChatGPT